In Vitro Toxicity Test of Ageratum Conyzoides L Extract and Adenostemma Lavenia Extract using BSLT Method - Aulia, Muti; Indriaty; Pandia, Ekariana S (Program Studi Biologi, Fakultas Teknik, Universitas Samudra, 2025)
Ageratum conyzoides L. and Adenostemma lavenia are known to contain bioactive compounds with potential therapeutic properties. This study aimed to determine the phenolic and flavonoid contents, as well as the toxicity of leaf extracts from both species against Artemia salina larvae. The extraction process was carried out using methanol as a solvent. Phenolic content was measured using the Folin-Ciocalteu method, while flavonoid content was determined through a colorimetric method using aluminum chloride (AlCl₃) reagent. Toxicity testing was performed using the Brine Shrimp Lethality Test (BSLT) method. The results showed that the methanolic extract of Ageratum conyzoides L. contained 173 mg GAE/g extract of phenolics and 55.45 mg QE/g extract of flavonoids, which were higher than those found in Adenostemma lavenia, with 73.8 mg GAE/g extract of phenolics and 6.33 mg QE/g extract of flavonoids. Toxicity test results analyzed using probit analysis revealed LC₅₀ values of 43.17 μg/mL for Ageratum conyzoides L. extract and 208.07 μg/mL for Adenostemma lavenia extract, indicating that both are toxic. Based on these findings, it can be concluded that Ageratum conyzoides L. possesses greater potential as a source of bioactive compounds, as indicated by its higher toxic activity. Both plants are considered worthy of further investigation as potential anticancer agents.